The Effect of Sisha on Respiratory Health - Hayatun Naimah; Ami Kallistasari; Cut Rahma Fazwa Emas Anda; Iqbal Mochtar (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Smoking sisha is considered a more socially acceptable activity in Middle East. The prevalence of sisha smokers varies among adolescent in the Middle East. Smoking sisha involves burning tobacco with a certain aroma, commonly referred to as molasses, and burning it using coal. Some people consider sisha a safer alternative to cigarettes, but some of evidence show the harmful and detrimental respiratory health effects associated with the use of sisha.